2012
DOI: 10.1128/jvi.00732-12
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Phosphorylation of Specific Serines and Threonines in the NS1 Protein of Human Influenza A Viruses

Abstract: We demonstrate that phosphorylation of the NS1 protein of a human influenza A virus occurs not only at the threonine (T) at position 215 but also at serines (Ss), specifically at positions 42 and 48. By generating recombinant influenza A/Udorn/72 (Ud) viruses that encode mutant NS1 proteins, we determined the roles of these phosphorylations in virus replication. At position 215 only a T-to-A substitution attenuated replication, whereas other substitutions (T to E to mimic constitutive phosphorylation, T to N, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
57
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 21 publications
3
57
1
Order By: Relevance
“…This in turn would permit NS1 to participate in specific protein-protein or RNA-protein interactions that allow for the known multifunctionality of NS1 (7). Such conformational plasticity could provide a mechanism for auto-regulating NS1 functions, depending on its temporal distribution, posttranslational modifications (phosphorylation [36,37] and sumoylation [38,39]), and nuclear or cellular localization, during the course of virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…This in turn would permit NS1 to participate in specific protein-protein or RNA-protein interactions that allow for the known multifunctionality of NS1 (7). Such conformational plasticity could provide a mechanism for auto-regulating NS1 functions, depending on its temporal distribution, posttranslational modifications (phosphorylation [36,37] and sumoylation [38,39]), and nuclear or cellular localization, during the course of virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation was the first posttransla-tional modification described to affect NS1 (25), and although early reports established that NS1 phosphorylation is important for efficient viral replication (26,27), a recent study provided strong evidence that, at least for the A/Udorn/72 virus strain, only one out of three identified phosphorylation events affects NS1's functions (28). Two additional posttranslational modifications affecting NS1 were almost simultaneously described, both belonging to the group of UBL proteins (proteins exhibiting a tertiary structure similar to that of ubiquitin).…”
mentioning
confidence: 99%
“…Knockdown experiments in human cells revealed that physiological levels of PPP6C are required for efficient virus growth and for transcription and replication of the viral genome, suggesting an important role for PP6 and for the regulation of phosphorylation in the influenza A virus life cycle. Indeed, previous studies have identified numerous sites of phosphorylation in the proteomes of influenza A and B viruses, with roles for phosphorylation being implicated in virus entry and exit, nuclear localization, and protein oligomerization (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49).…”
mentioning
confidence: 99%